(untitled) (Journal of the College of Basic Education, 2020)
The present study aimed to detect the effects of (Citral , Crcumin, Inulin, Resveratrol, Trans-cinnamaldhyde) compounds on biofilm formation of Cronobacter sakazakii by uses microtiter plate method . Seventeen isolates of C. sakazakii from different clinical isolates and milk sourses were collected from previous study. All isolates were identified depending on 16S rRNA gene The addition of (Citral, Curcumin, Inulin , Resveratrol, Trans-cinnamaldhyde) at concentration (50, 100) microgram/ml was coulde inhibition biofilm formation based on isolate sourse and compound concentration .